PENGARUH PELATIHAN TERHADAP PRESTASI KERJA KARYAWAN DI GRAND INNA HOTEL PADANG - atika prasuri (JURNAL PENDIDIKAN DAN KELUARGA, 2018)
Based on this study to determine the effect of training on employees work performance at Grand Inna Hotel Padang. This type of research_is causal associative. The sample used is total sampling, which is as many as 60 employees who are in the operational section, through a questionnaire with a Likert scale whose validity and reliability have been tested. The results obtained from this study are as follows: (1) training is in the very good category 68.33%, (2) employees work performance is in a very good category of 95%, (3) the results of testing a simple linear regression hypothesis obtained F for 8.649 with sig. 0.00 <0.05, then the training variable explains the variable employees performance of 13% and 87% influenced by other factors. Then the coefficient value of 0.248 is obtained with the value in sig. 0.00 <0.05. This means that each increase of 1 training unit will increase the 0.248 work achievement units of Grand Inna Hotel Padang employees. Keywords: Training, Employee Performance